Protocol for a single patient therapy plan: A randomised, double‐blind, placebo‐controlled N‐of‐1 trial to assess the efficacy of cannabidiol in patients with intractable epilepsy. (23rd September 2020) - Ong, Katherine S; Carlin, John B; Fahey, Michael; Freeman, Jeremy L; Scheffer, Ingrid E; Gillam, Lynn; Anderson, Monique; Huque, Md Hamidul; Legge, Donna; Dirnbauer, Nicole; Lilley, Brian; Slota‐Kan, Simon; et al.
Abstract : Aim: This paper describes the use of the single patient therapy plan (SPTP). The SPTP has been designed to assess the efficacy at an individual level of a commercially available cannabinoid product, cannabidiol, in reducing seizure frequency in paediatric patients with intractable epilepsy. Methods: The SPTP is a randomised, double‐blind, placebo‐controlled N‐of‐1 trial designed to assess the efficacy of treatment in a neurology outpatient setting. The primary objective of the SPTP is to assess the efficacy of cannabidiol in reducing seizure frequency in each patient with intractable epilepsy, with change in seizure frequency being the primary outcome of interest. The analysis adopts a Bayesian approach, which provides results in the form of posterior probabilities that various levels of benefit (based on the primary outcome measure, seizure frequency) have been achieved under active treatment compared to placebo, accompanied by decision rules that provide thresholds for deciding whether treatment has been successful in the individual patient. The SPTP arrangement is most accurately considered part of clinical practice rather than research, since it is aimed at making clinical treatment decisions for individual patients and is not testing a hypothesis or collecting aggregate data. Therefore, Human Research Ethics Committee approval was considered not to be required, although it is recommended that hospital Clinical Ethics Committees provide ethical oversight. Conclusion: These SPTP resources are made available so that they may inform clinical practice in the treatment of severe epilepsy or adapted for use in other conditions.